The bioelements, the elementome, and the biogeochemical niche - Peñuelas, Josep; Fernández-Martínez, Marcos; Ciais, Philippe; Jou, David; Piao, Shilong; Obersteiner, Michael; Vicca, Sara; Janssens, Ivan A.; Sardans, Jordi (Ecology (Durham), 2019)
Every living creature on Earth is made of atoms of the various bioelements that are harnessed in the construction of molecules, tissues, organisms, and communities, as we know them. Organisms need these bioelements in specific quantities and proportions to survive and grow. Distinct species have different functions and life strategies, and have therefore developed distinct structures and adopted a certain combination of metabolic and physiological processes. Each species is thus also expected to have different requirements for each bioelement. We therefore propose that a “biogeochemical niche” can be associated with the classical ecological niche of each species. We show from field data examples that a biogeochemical niche is characterized by a particular elementome defined as the content of all (or at least most) bioelements. The differences in elementome among species are a function of taxonomy and phylogenetic distance, sympatry (the bioelemental compositions should differ more among coexisting than among non-coexisting species to avoid competitive pressure), and homeostasis with a continuum between high homeostasis/low plasticity and low homeostasis/high plasticity. This proposed biogeochemical niche hypothesis has the advantage relative to other associated theoretical niche hypotheses that it can be easily characterized by actual quantification of a measurable trait: the elementome of a given organism or a community, being potentially applicable across taxa and habitats. The changes in bioelemental availability can determine genotypic selection and therefore have a feedback on ecosystem function and organization, and, at the end, become another driving factor of the evolution of life and the environment.